Aspek Perfektif Verba Majemuk Owaru dalam Bahasa Jepang (Universitas Negeri Jakarta, 2017)
The purpose of this study is to determine the meaning of the perfective aspect of and the structure of Japanese compound verbs ‘owaru’. The data used in this study were obtained from online newspaper, which analyzed using unified method that refers to the aspectuality theory. The result of the research show that verbs that attached to ‘owaru’ are continuative verbs (keizokudoushi) which contains ‘telik’ and ‘atelik’ meaning, and also have punctual verbs (shunkandoshi) which the activity of the verbs can be used continuatively. The meaning of the verbs show that the activity which done marked with another activity occurred, and the meaning of occurred activity were done intentionally by the agent (subject) without any relevance to the activity afterwards.